IMPLEMENTATION OF THE INDEPENDENT CURRICULUM IN IMPROVING SOFT SKILLS AND ABSORPTION OF GRADUATES VOCATIONAL SCHOOL - Suprianto, Arik; Wurianto, Arif Budi; Tinus, Agus (JURNAL EDUSCIENCE, 2025)
Purpose-This study aims to examine how the Independent Curriculum contributes to improving soft skills and the absorption of vocational high school graduates in the workforce. Methodology- The approach employed is a descriptive qualitative method, utilizing data collection techniques that include in-depth interviews, observations, and documentation at SMK Muhammadiyah 2 Malang which has implemented the Independent Curriculum. This technique involves the principal, deputy curriculum, and subject teachers. The data analysis employs the Miles and Huberman approach, specifically focusing on data reduction, data display, and conclusions.Findings - The study's results indicate that the implementation of the Independent Curriculum in vocational schools has been accompanied by Project-Based Learning (PjBL), and the flexibility of choosing subjects significantly provides students with space to develop essential soft skills, including communication, collaboration, and creativity. In addition, active collaboration between schools and industry in curriculum development and implementation of internship programs can also increase the relevance of student competencies according to job market needs. Vocational school graduates who participated in learning based on the Independent Curriculum demonstrated a higher level of adaptability and professionalism compared to those who followed the previous curriculum.Contribution - This study provides scientific facts about the implementation of the Independent Curriculum in improving soft skills and the absorption of vocational school graduates, so that it can be used as a reference and consideration for policies that will be taken both for the development of soft skills and the absorption of vocational school graduates.